2014
DOI: 10.7182/pit2014911
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Self-Management after Pediatric Heart Transplant

Abstract: The transition to self-management after heart transplant was a clear goal for both parents and adolescents. The transition is a shared responsibility between parents and adolescents with a gradual shift from parent-directed to self-management. The process of transition was not linear or smooth, and in several instances, parents described efforts to transfer responsibility to the adolescent only to take it back when complications arose. Additional research with a larger sample is needed in order to fully unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Some aspects of self‐management were taken on gradually by children, including managing medication, therapies, and procedures (Buford, ; Meaux et al, ; Williams, Mukhopadhyay, Dowell, & Coyle, ), whereas skills such as decision making and liaising with services needed to be acquired suddenly on transfer to adult services (Kirk, ). The parent‐to‐child transfer of self‐management responsibility was modelled in various ways; some studies reported that the child, the parent or both, sequentially progressed through discrete stages (Babler & Strickland, ; Schilling, Knafl, & Grey, ) whereas others viewed the transfer as a fluid, bidirectional continuum where child and parental roles and responsibilities were regularly shifting (Chilton & Pires‐Yfantouda, ; Williams et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some aspects of self‐management were taken on gradually by children, including managing medication, therapies, and procedures (Buford, ; Meaux et al, ; Williams, Mukhopadhyay, Dowell, & Coyle, ), whereas skills such as decision making and liaising with services needed to be acquired suddenly on transfer to adult services (Kirk, ). The parent‐to‐child transfer of self‐management responsibility was modelled in various ways; some studies reported that the child, the parent or both, sequentially progressed through discrete stages (Babler & Strickland, ; Schilling, Knafl, & Grey, ) whereas others viewed the transfer as a fluid, bidirectional continuum where child and parental roles and responsibilities were regularly shifting (Chilton & Pires‐Yfantouda, ; Williams et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The parent‐to‐child transfer of self‐management responsibility was modelled in various ways; some studies reported that the child, the parent or both, sequentially progressed through discrete stages (Babler & Strickland, ; Schilling, Knafl, & Grey, ) whereas others viewed the transfer as a fluid, bidirectional continuum where child and parental roles and responsibilities were regularly shifting (Chilton & Pires‐Yfantouda, ; Williams et al, ). For example, in some families, parents would resume management of the LTC when their child was tired, unwell, or lacking motivation (Kirk, ; Schilling et al, ) or when complications arose (Meaux et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…to adherence and the transition to self-management in adolescents and young adults. A recent pilot study used online focus groups and asked adolescents and parents of adolescents to report their perceptions and difficulties with integrating self-management on a daily basis and transitioning their child from parent-delivered care to self-care, respectively [21]. A patient-centered approach to identifying areas of interest and areas where specific interventions can target gaps in current health management can improve outcome beyond survival.…”
Section: Outcome Goals Beyond Survival In Pediatric Heart Failure Andmentioning
confidence: 99%
“…As pediatric heart transplant continues to increase long‐term survival rates, recipients must learn how to manage their complex medical regimen. To increase transition success, pediatric providers and caregivers must assist in the transition process and transfer of medical care to the adult provider and responsibility of medical care to the patient . The transition process involves a multitude of educational steps, shifts in responsibility and patient self‐management, and a sense of autonomy to increase successful transition .…”
Section: Introductionmentioning
confidence: 99%
“…To increase transition success, pediatric providers and caregivers must assist in the transition process and transfer of medical care to the adult provider and responsibility of medical care to the patient. 2 The transition process involves a multitude of educational steps, shifts in responsibility and patient self-management, and a sense of autonomy to increase successful transition. 3,4 The goal of transition is to educate and prepare pediatric patients for their transfer of medical care to an adult provider.…”
Section: Introductionmentioning
confidence: 99%